2022
DOI: 10.1177/0308518x221141427
|View full text |Cite
|
Sign up to set email alerts
|

Territorial stigmatization and housing commodification under racial neoliberalism: The case of Denmark's ‘ghettos’

Abstract: The relation between racialization and neoliberalism is relatively unexplored in urban geography, especially in the context of social democratic welfare regimes. This article aims to bridge this gap by applying the concept of racial neoliberalism, here referring to a co-constitutive relation between racialization and neoliberalism, to Denmark. Conceiving the country's so-called ‘ghetto’ politics as an expression of racial neoliberalism, the article retraces the development of this politics over the first two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Therefore, through the racial neoliberal urbanism that the Ghetto Package is an example of, we also see how certain ideas are implicit about who is displaceable and who is desirable, which go beyond the specific interventions, so much that nobody even seems to question it: the predominant subject is the White male in all the proposed developmental plans. Now, obviously this rests on previous processes of racialization that goes beyond the specific law as such (as several authors such as Risager, 2022b;Olsen andLarsen, 2022 andSimonsen, 2016 have shown very elegantly), but more importantly, it also goes beyond Danish society and point at tendencies that one might argue are more common for urban planning in general (much like authors such as Giovanni Picker et al, 2019, and Ha and Picker 2022 seem to suggest), but also to the neoliberal Capitalist State in its management of poverty and more importantly the so-called surplus populations (Lundsteen, 2020;Smith, 2011;Soederberg, 2021;Wacquant, 2010).…”
Section: Mjølnerparkenmentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, through the racial neoliberal urbanism that the Ghetto Package is an example of, we also see how certain ideas are implicit about who is displaceable and who is desirable, which go beyond the specific interventions, so much that nobody even seems to question it: the predominant subject is the White male in all the proposed developmental plans. Now, obviously this rests on previous processes of racialization that goes beyond the specific law as such (as several authors such as Risager, 2022b;Olsen andLarsen, 2022 andSimonsen, 2016 have shown very elegantly), but more importantly, it also goes beyond Danish society and point at tendencies that one might argue are more common for urban planning in general (much like authors such as Giovanni Picker et al, 2019, and Ha and Picker 2022 seem to suggest), but also to the neoliberal Capitalist State in its management of poverty and more importantly the so-called surplus populations (Lundsteen, 2020;Smith, 2011;Soederberg, 2021;Wacquant, 2010).…”
Section: Mjølnerparkenmentioning
confidence: 96%
“…Be that as it may, the purpose of this article has not been to argue the contrary, nor go into further detail, but rather argue that the three different interpretations put forward in the introduction are best understood in co-relation to each other. Although gentrification is indeed proposed as a measure to promote social mix, at the same time promoting and implying neoliberal ideas regarding marketization, privatization and the social in general, at the same time, in line with what authors such as Risager (2022b) and Mele (2019) argue, these ideas and projects are inexplicable without reference to racialization and the territorial stigmatization enacted by the law. Furthermore, they both connect to a larger, more abstract vision of the Danish society and maybe even Western liberal societies by large, because through these urban transformations and this social experiment, certain moralities, and moral communities of belonging, are being put in force.…”
Section: Mjølnerparkenmentioning
confidence: 99%
See 3 more Smart Citations